Characterization and Biofilm Formation of Pediatric Staphylococcus aureus Device-related Infection Isolates Compared with Skin and Soft-tissue infection Isolates from 2008 to 2016. (4th October 2017) - Foster, Catherine; Kok, Melissa; Mason, Edward O; Kaplan, Sheldon L; Hulten, Kristina G
Abstract: Background: S. aureus device-related infections (DRIs) cause substantial pediatric morbidity and hospitalization costs. Biofilm formation is postulated to play an important role in the pathogenesis of DRIs. We hypothesized that S. aureus isolates from DRIs would differ in antibiotic susceptibility, genotype, and ability to form biofilm in vitro compared with skin and soft-tissue infection (SSTI) isolates. Methods: Patients at Texas Children's Hospital (TCH) and their isolates were identified from a prospective S. aureus study database from 2008 to 2016. Age and date of infection matched SSTI control isolates were selected 4:1. Demographic and clinical data was collected retrospectively. Isolates were genotyped by pulsed field gel electrophoresis. In vitro biofilm formation was assessed for DRI and a subset of SSTI isolates using a modified microtiter plate assay and scoring system (APMIS 2007;115:891–9). Data was analyzed with Fisher's exact or Wilcoxon rank-sum test. Results: DRIs from 47 patients (Figure 1) and SSTIs from 188 patients were identified. Thirty (64%) patients developed infections within 90 days of device placement. The perioperative antibiotic used most often was cefazolin (92%). Patients with DRIs were hospitalized for a median of 10 days (range 1, 45). Polymicrobial infections were identified in 6 patients and 3 patients were bacteremic. Of the 47 DRI isolates, 35 (74%) were MSSA and 40 (87%) were nonUSA300 vs. the 188 SSTI isolates of which 79 (42%) were MSSA and 56 (30%) were nonUSA300 (P <0.0001 for both). Biofilm formation was assessed for 47 DRI and 33 SSTI isolates. Among the DRI isolates, 37 (79%) were strong or very strong biofilm producers, while all the SSTI isolates were strong or very strong (Figure 2). Conclusion: S. aureus DRI isolates were significantly more likely to be MSSA and nonUSA300 compared with SSTI isolates. Using this biofilm model, isolates from DRIs were less likely to be associated with very strong biofilm production than SSTIs. We speculate that biofilm phenotype ( ica dependent vs surface proteins) may play a more important role than level of production in pathogenesis of pediatric S. aureus DRIs (J Clin Microbiol 2007;70:698–703). Our findings may have implications for developing strategies to prevent S. aureus DRIs. Disclosures: S. L. Kaplan, Pfizer: Grant Investigator and Speaker at PCV13 Launch Meeting in China, Research grant and Speaker honorarium